Repotenciación de un sistema automatizado de riego y control de humedad, dentro del invernadero #2 del Centro Experimental Salache en la Universidad Técnica de Cotopaxi. - Siza Jami, Edwin Paul (2020)
The present project was carried out in the greenhouse #2 of the "Centro Experimental Académico Salache", of the Technical University of Cotopaxi, located in the Cotopaxi province, Latacunga canton, Salache parish, with the objective of repowering the automated system of irrigation and humidity control in the four sections, by means of the reconfiguration of the programming algorithm and the acquisition of new sensors, which allowed us to control the variable depending on the humidity that varies according to the type of cultivation, this way the yield and the quality of the products have been improved. This automated irrigation system has electrical and electronic equipment such as, PLC S7 1200, analog input module, water pumps and RS485 sensors, these sensors are responsible for detecting the humidity in each section of the greenhouse, sending a signal to the electro valves for the subsequent process of opening or closing the water resource, in this way you can control the humidity variable, manually or automatically through the HMI screen where you can view the data obtained by the sensors. With this project it was possible to take advantage of a more efficient way of the hydric resource, and to supply in suitable quantities depending on the type of culture that one has, which will facilitate the students of Agronomy major, so that they can realize their respective skills in the greenhouse of study and improve their productivity.